A Bibliometric Analysis of Best Practices on The Food Security Strategy to Economic Resilience - Utami, Anisa Fitria; Triandini, Noer Aida; Nadofah (Journal of Economics, Business, and Government Challenges, 2025)
Food security has remained a global concern, despite efforts in the international goal to eliminate food insecurity during the last few decades. However, the subjective dimension of food security has received little attention in food security research. Research Methods: This article provides detailed procedural directions for (i) combining and cleaning bibliometric data from several databases (Scopus and Web of Science) and (ii) doing bibliometric analysis with multiple tools (bibliometrix and VOSviewer). Then, We used bibliometric analytic techniques with regard to document type, subject area, author, and country of publishing. Finding/Results: The study's findings reflect research trends, highlight major research obstacles, and suggest prospective areas for future research in this fascinating field. Conclusion: The results show an increase in studies on food security strategies, especially during the Covid-19 pandemic, due to the increasing global awareness of challenges such as climate change and population growth. China is the country with the highest number of publications on food security strategies. Research on food security strategies is multidisciplinary, involving economic, environmental, and social aspects, so multidisciplinary and global collaboration is needed.